Health-Related Gender Knowledge: Scale Development and Validation in Spanish Nursing Students - Sara Prego-Jimenez; Jone Aliri; Olatz Goñi-Balentziaga; Eva Pereda-Pereda; Ainitze Labaka (Nursing Reports, 2025)
Background/Objectives: Gender bias in healthcare remains a persistent challenge, partly due to gaps in gender-related knowledge among professionals. While existing instruments assess gender sensitivity and gender-role ideology, there is a lack of generalizable tools specifically designed to evaluate gender-related health knowledge. This study aimed to develop and validate the Gender Knowledge Scale in a sample of 591 nursing students from the University of the Basque Country (Spain). Methods: The 10-item multiple-choice instrument was created using the Nominal Group Technique with a multidisciplinary panel of experts. Results: Psychometric analyses supported a unidimensional structure with acceptable fit indices (CFI = 0.928, RMSEA = 0.025), and items displayed a diverse range of difficulty levels. Knowledge scores were moderately correlated with gender sensitivity but not with gender-role ideology, suggesting that knowledge may influence attitudes but is insufficient to challenge entrenched stereotypes. Knowledge differences emerged across academic years, though not by gender. Misconceptions, particularly regarding menstruation, cardiovascular risk, and pain, were prevalent. Conclusions: The Gender Knowledge Scale is a practical and psychometrically sound tool for assessing gender-related health knowledge among nursing students. While further validation is needed in other populations, the scale may support educational interventions aimed at reducing gender bias in clinical care.